Psychological Capital and Transformational Leadership: Insights from Islamic School Principals - Millah, Kunkun Syaeful (Darussalam: Journal of Psychology and Educational, 2025)
This study explores the relationship between psychological capital and transformational leadership among Islamic school principals. Psychological capital, consisting of hope, efficacy, resilience, and optimism, has been widely recognized as a positive psychological resource that enhances leadership effectiveness. Drawing on a mixed-method approach, data were collected through surveys and semi-structured interviews involving principals from various Islamic schools. Quantitative analysis revealed a significant positive correlation between the dimensions of psychological capital and the four components of transformational leadership: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. Qualitative findings further highlight that principals who cultivate strong psychological capital demonstrate greater adaptability, empathy, and vision in managing educational challenges within faith-based contexts. The study provides insights into the role of inner psychological resources in shaping effective transformational leadership, particularly in Islamic educational institutions. These findings underscore the importance of training programs aimed at strengthening psychological capital as a strategy to foster visionary and value-driven leadership